Family Support in Treating Elderly with PTM in the Time of the Covid-19 Pandemic - Yetti Syafridawita; Agus Setiawan (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The family is the closest person to the elderly and plays an essential role in caring for the elderly with PTM during the covid-19 pandemic. This article aims to determine family support in caring for the elderly with non-communicable diseases (PTM) during the COVID-19 pandemic. This study conducts a systematic review of online databases, including Science Direct, Proquest, Clinicalkey, and Google Sholar. The keywords used are “family support”, “elderly”, “covid-19”, and “non-communicable disease”. The literature search was conducted in English and Indonesian from 2012 to 2021. The results obtained were an analysis of 10 research articles related to family support for caring for the elderly. The weakness that may arise in this research is that there may still be some relevant articles that do not meet the inclusion criteria set by the author. Family support in caring for the elderly with non-communicable diseases (PTM) is very much needed during the Covid-19 pandemic. This study was designed to review literature related to family support in caring for the elderly with PTM during the Covid19 pandemic.